Reconstructing Public Opinion through Informal Community Leadership in the Age of Fragmented Authority - Irfan, Mochamad (Metromedia, 2025)
This study investigates the sociological function of informal leadership figures in shaping public opinion within community environments. It aims to identify and analyze the mechanisms such as cultural proximity, symbolic capital, and interpersonal trust that enable these figures to act as intermediaries between communities and broader political or informational narratives. Through a literature review approach, it examines how individuals who are not formally elected or institutionally appointed nonetheless exert substantial influence on collective perception and civic behavior. The research identifies key mechanisms such as cultural proximity, symbolic capital, and interpersonal trust that position these figures as intermediaries between communities and broader political or informational narratives. As formal structures of communication become increasingly fragmented, these informal voices fill the gap, translating complexity into shared meaning and mobilizing communal responses. The paper also explores how these dynamics are amplified in digital spaces, where traditional hierarchies of communication are disrupted. Findings suggest that understanding the emergence and function of informal leadership is crucial to grasp the true contours of public discourse, particularly in societies where institutional trust is volatile or contested. This study contributes to the academic discourse by integrating classical and contemporary theories to provide a conceptual foundation for further empirical investigation.